The sickle cell trait affects contact dynamics and endothelial cell activation in Plasmodium falciparum-infected erythrocytes. (December 2018) - Lansche, Christine; Dasanna, Anil; Quadt, Katharina; Fröhlich, Benjamin; Missirlis, Dimitris; Tétard, Marilou; Gamain, Benoit; Buchholz, Bernd; Sanchez, Cecilia; Tanaka, Motomu; Schwarz, Ulrich; Lanzer, Michael
Abstract Sickle cell trait, a common hereditary blood disorder, protects carriers from severe disease in infections with the human malaria parasitePlasmodium falciparum . Protection is associated with a reduced capacity of parasitized erythrocytes to cytoadhere to the microvascular endothelium and cause vaso-occlusive events. However, the underpinning cellular and biomechanical processes are only partly understood and the impact on endothelial cell activation is unclear. Here, we show, by combining quantitative flow chamber experiments with multiscale computer simulations of deformable cells in hydrodynamic flow, that parasitized erythrocytes containing the sickle cell haemoglobin displayed altered adhesion dynamics, resulting in restricted contact footprints on the endothelium. Main determinants were cell shape, knob density and membrane bending. As a consequence, the extent of endothelial cell activation was decreased. Our findings provide a quantitative understanding of how the sickle cell trait affects the dynamic cytoadhesion behavior of parasitized erythrocytes and, in turn, endothelial cell activation. Christine Lansche, Anil Dasanna et al. investigate the dynamic cytoadhesion behavior of erythrocytes infected with malaria parasite using quantitative flow chamber experiments and computer simulations. They find that parasitized erythrocytes have altered adhesion dynamics, mainly due to differences in cell shape, knob density and membrane bending.